2017
DOI: 10.1039/c7ta05503j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen containing carbon spheres as an efficient electrocatalyst for oxygen reduction: Microelectrochemical investigation and visualization

Abstract: A fast-scanning ultramicroelectrode probe is employed to trace the mechanistic pathway followed by the designed nitrogen containing carbon spheres in highly alkaline medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…measured current density; j l -diffusion-limiting current density; j k -kinetic-limiting current; ω-electrode rotation rate (rpm); F-Faradaic constant (96,485 C/mol); C O2 -O 2 concentration in 1M NaOH solution (0.843 × 10 −6 mol/cm 3 ); D O2 -O 2 diffusion in 1M NaOH solution (1.43 × 10 −5 cm 2 /s); n-number of electrons transferred in the ORR process; ν-kinematic viscosity of the electrolyte (1.13 × 10 −2 cm 2 /s)[30][31][32].…”
mentioning
confidence: 99%
“…measured current density; j l -diffusion-limiting current density; j k -kinetic-limiting current; ω-electrode rotation rate (rpm); F-Faradaic constant (96,485 C/mol); C O2 -O 2 concentration in 1M NaOH solution (0.843 × 10 −6 mol/cm 3 ); D O2 -O 2 diffusion in 1M NaOH solution (1.43 × 10 −5 cm 2 /s); n-number of electrons transferred in the ORR process; ν-kinematic viscosity of the electrolyte (1.13 × 10 −2 cm 2 /s)[30][31][32].…”
mentioning
confidence: 99%
“…When nitrogen is incorporated into graphitic carbon materials, the strong electronegativity of nitrogen atoms enriches the surrounding electrons, and makes adjacent carbon atoms positively charged, which is beneficial to the adsorption of oxygen molecules, thereby promoting the process of oxygen reduction reaction, and improving the catalytic activities of the carbon materials. [42] In addition, the catalytic activity of the Fe-free catalyst is greatly reduced compared with the Fe-containing catalysts, verifying the importance of Fe in the catalyst's ORR activity. Moreover, the spent graphite was found to contain tiny amounts of transition metals and defects in the sample preparation, which is conducive to in situ doping with N and transition metal atoms.…”
Section: Resultsmentioning
confidence: 94%
“…The low amount of intermediate produced (20% in neutral and 10% in alkaline solution) suggested that the electron transfer occurred mostly through a four-electron transfer at both pHs. 137 Some groups have studied electrocatalysts that are metalfree, such as Tiwari et al 138 who have evaluated the performance of nitrogen-bearing carbon spheres (NCSs) synthesized at 600, 800 and 900 C (NCS-600, NCS-800 and NCS-900). The application of metal free carbon-based nanomaterials in electrocatalysis has emerged recently, thanks to their good conductivity, high surface area and stability.…”
Section: Oxygen Reduction Reaction (Orr)mentioning
confidence: 99%